The recycling of chromitites in ophiolites from southwestern North America - González-Jiménez, J.; Camprubí, A.; Colás, V.; Griffin, W.; Proenza, J.; O'Reilly, S.; Centeno-García, E.; García-Casco, A.; Belousova, E.; Talavera, Cristina; Farré-de-Pablo, J.; Satsukawa, T. (Elsevier BV, 2017)
© 2017 Elsevier B.V. Podiform chromitites occur in mantle peridotites of the Late Triassic Puerto Nuevo Ophiolite, Baja California Sur State, Mexico. These are high-Cr chromitites [Cr# (Cr/Cr + Al atomic ratio = 0.61–0.69)] that contain a range of minor- and trace-elements and show whole-rock enrichment in IPGE (Os, Ir, Ru). That are similar to those of high-Cr ophiolitic chromitites crystallised from melts similar to high-Mg island-arc tholeiites (IAT) and boninites in supra-subduction-zone mantle wedges. Crystallisation of these chromitites from S-undersaturated melts is consistent with the presence of abundant inclusions of platinum-group minerals (PGM) such as laurite (RuS 2 )-erlichmanite (OsS 2 ), osmium and irarsite (IrAsS) in chromite, that yield T MA ˜ T RD model ages peaking at ~ 325 Ma. Thirty-three xenocrystic zircons recovered from mineral concentrates of these chromitites yield ages (2263 ± 44 Ma to 278 ± 4 Ma) and Hf-O compositions [? Hf (t) = - 18.7 to + 9.1 and 18 O values < 12.4‰] that broadly match those of zircons reported in nearby exposed crustal blocks of southwestern North America. We interpret these chromitite zircons as remnants of partly digested continental crust or continent-derived sediments on oceanic crust delivered into the mantle via subduction. They were captured by the parental melts of the chromitites when the latter formed in a supra-subduction zone mantle wedge polluted with crustal material. In addition, the Puerto Nuevo chromites have clinopyroxene lamellae with preferred crystallographic orientation, which we interpret as evidence that chromitites have experienced high-temperature and ultra high-pressure conditions ( < 12 GPa and ~ 1600 °C). We propose a tectonic scenario that involves the formation of chromitite in the supra-subduction zone mantle wedge underlying the Vizcaino intra-oceanic arc ca. 250 Ma ago, deep-mantle recycling, and subsequent diapiric exhumation in the intra-oceanic basin (the San Hipólito marginal sea) generated during an extensional stage of the Vizcaino intra-oceanic arc ca. 221 Ma ago. The T RD ages at ~ 325 Ma record a partial melting event in the mantle prior to the construction of the Vizcaino intra-oceanic arc, which is probably related to the Permian continental subduction, dated at ~ 311 Ma.